The Practice of Presidential Succession in Indonesia - Dian Aries Mujiburohman (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2020)
This study analyzed Article 8 of the 1945 Constitution of the Republic of Indonesia on the presidential succession in Indonesia. The 1945 Constitution clearly regulates presidential and vice-presidential election period for once in five years. However, the practice of presidential succession can be unpredictable. This article aims to elaborate the management of presidential succession in Indonesia. The study in this article employed normative research method by applying a statute approach. The finding of the study proves that based on Article 8 of the 1945 Constitution; there are four circumstances of presidential substitutions. They are decease, resignation, dismissal, and inability to carry out duties. However, in the actual practices that have been happened several times, the presidential successions in Indonesia were not always caused by the four conditions. The examples are the successions of Soekarno, Soeharto, and Abdurrahman Wahid. The three Presidents were dismissed without transparent legal reasons. Their dismissals were based merely on political decisions, not legal reasons. In addition, political transitions, internal conflicts, and economic crises contributed to the presidential successions in Indonesia.Praktik Pergantian Jabatan Presiden di IndonesiaAbstrakArtikel ini menganalisis Pasal 8 Undang-Undang Dasar Negara Republik Indonesia (UUD NRI 1945) terkait dengan pergantian presiden di Indonesia. Pengaturan mengenai pemilihan presiden dan wakil presiden dalam undang-undang dasar sudah jelas kapan waktunya, yaitu lima tahun sekali. Akan tetapi, pergantian presiden merupakan peristiwa yang tidak dapat diprediksi kapan akan terjadi. Artikel ini bertujuan untuk menelaah bagaimana sesungguhnya sistem pemerintahan Indonesia mengatur pergantian presiden. Temuan ini membuktikan bahwa sesuai dengan Pasal 8 UUD NRI 1945 terdapat  empat peristiwa pergantian presiden, yaitu mangkat, berhenti, diberhentikan dan tidak dapat melakukan kewajibannya. Namun, dalam praktek keempat peristiwa pergantian presiden tersebut tidak benar-benar diterapkan sebagaimana pergantian presiden yang terjadi pada masa pemerintahan Presiden Soekarno, Soeharto dan Abdurrahman Wahid. Ketiga presiden tersebut mengalami pergantian presiden tanpa alasan hukum yang jelas, semata-mata didasarkan atas keputusan politik ketimbang alasan-alasan hukum. Selain itu, transisi politik, pergolakan dalam negeri dan krisis ekonomi ikut mengiringi  pergantian presiden di Indonesia.Kata kunci: jabatan presiden, pergantian presiden, Undang-Undang Dasar 1945.DOI: https://doi.org/10.22304/pjih.v7n2.a6